Age and sport are associated with higher odds of playing through a concussion and delayed removal from play. Issue 11 (25th May 2017) - Zuckerman, Scott L; Kuhn, Andrew W; Yengo-Kahn, Aaron M; Kerr, Zachary Y; Totten, Doug J; Solomon, Gary S; Sills, Allen K
Abstract : Objective: To elucidate situational factors and individual characteristics related to playing through a sport-related concussion (SRC) and delayed removal from play. Design: Retrospective cross-sectional analysis. Setting: A single comprehensive sports-concussion centre. Participants: 250 middle school, high school, and collegiate athletes who sustained an SRC and presented to a regional concussion center between 2011 and 2015. Intervention: Standardised in-depth phone interviews. Outcome measures: Gender, race, age, competition level, sport, concussion history, practice/game, and collision awareness, among other variables, were incorporated into a multivariate regression model to determine if any of these variable could significantly predict the likelihood of playing through a sport-related concussion versus immediate removal from play. Main results: Age (p=0.047) and sport (p=0.006) were both significantly associated with playing through a concussion. For every additional year of age, the odds of playing through an SRC decreased by 1.32 [95% CI: 1.00–1.72]. Football players were much more likely to attempt to "play through" a concussion when compared to baseball/softball, basketball, cheerleading, lacrosse, rugby and volleyball athletes (OR 5.41 [95% CI: 1.62–18.2] to 71.4 [95% CI: 4.93–1, 000] times the odds of playing through an SRC for various sports, with all differences reaching statistical significance). Conclusions: Younger age and certain sports (football) were significantly associated with delayed removal from play after a SRC in middle school, high school, and collegiate athletes. Given these results, sports medicine practitioners may be better able to identify situational and individual characteristics of athletes who may be more likely play through a SRC. Competing interests: GS Solomon receives consulting fees from the Tennessee Titans (NFL), the Nashville Predators (NHL), and the athletic departments of several universities, all fees paid to institution. In addition he is a member of the ImPACT Scientific Advisory Board, and receives reimbursement for expenses to board meetings. AK Sills is a consulting physician to the Nashville Predators (uncompensated) and also serves as an unaffiliated neurotrauma consultant for the NFL. SL Zuckerman, AW Kuhn, AM Yengo-Kahn, ZY Kerr, DJ Totten, report no conflicts of interest.